Feed utilization during late gestation by polled Hereford and Simmental cows - Schalles, R.R.; Kiracofe, G.H.; Wright, J.W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty-one Polled Hereford and 29 Simmental cows were individually fed two energy levels for about the last 4 months before calving. Weight, condition score, backfat thickness, and reproduction were evaluated. No differences were found in efficiency of feed utilization between breeds or between energy levels. These cows started the experiment in moderate body condition, and a 10% reduction in dietary energy level during late gestation did not affect their reproductive performance.
Keywords: Beef; Feed; Gestation; Hereford cows; Simmental cows